Mitochondrial Dysfunction and Kidney Stone Disease - Chaiyarit, Sakdithep; Thongboonkerd, Visith (Frontiers in Physiology, 2020)
Mitochondrion is a pivotal intracellular organelle that plays crucial roles in regulation of energy production, oxidative stress, calcium homeostasis and apoptosis. Kidney stone disease (nephrolithiasis/urolithiasis), particularly calcium oxalate (CaOx) (the most common type), has been shown to be associated with oxidative stress and tissue inflammation/injury. Recent evidence has demonstrated the involvement of mitochondrial dysfunction in CaOx crystal retention and aggregation as well as Randall’s plaque formation, all of which are the essential mechanisms for kidney stone formation. This review highlights the important roles of mitochondria in renal cell functions and provides the data obtained from previous investigations of mitochondria related to kidney stone disease. In addition, mechanisms for the involvement of mitochondrial dysfunction in the pathophysiology of kidney stone disease are summarized. Finally, future perspectives on the novel approach to prevent kidney stone formation by mitochondrial preservation are discussed.